The Effect of the Benson Relaxation Technique on Blood Pressure in the Elderly - Vincencius Surani; Lilik Pranata; Sri Indaryati; Keristina Ajul; Srimiati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The problem that often occurs in the elderly is changes in blood pressure. The condition of blood pressure that often occurs is hypertension. This study aims to analyze the impact of benson relaxation techniques on blood pressure in the elderly. This research is a quantitative study with a one group pretest-posttest (pre-experimental) design. The number of samples in this study was 30 respondents with a sampling technique using total sampling. The data collection tool used a questionnaire which consisted of a survey on the characteristics of the respondents, an aneroid sphygmomanometer, and a stethoscope. The intervention used is the Benson relaxation technique. Data collection was carried out before and after the implementation of the intervention. Research data were analyzed using the Wilcoxon Signed-Rank Test with a p-value <0.05. The conclusion in this study is that there are significant differences in elderly blood pressure before and after the intervention.